Multimedia foundations: : core concepts for digital design - Costello, Vic (New York : Routledge, Taylor & Francis Group, 2024)
"Whether you are working using text, graphics, photography, sound, motion, or video, Multimedia Foundations covers the skills necessary to be an effective modern storyteller. Presented in full colour with hundreds of vibrant illustrations, this book trains readers in the principles and skills common to all forms of digital media production, enabling the creation of successful, engaging content, no matter what tools are used. Chapters feature useful exercises to cement core concepts and help readers develop planning, collaboration, design, and production skills. This third edition has been fully updated and includes new and revised illustrations, updated coverage of digital asset management and media workflows, a completely rewritten chapter on coding for web and mobile media, and new sections on design thinking, inclusive design, colour theory, photography composition, interview and B-roll acquisition techniques, and editing stages and postproduction workflows. Multimedia Foundations is a comprehensive resource for students in fields such as journalism, film production, animation and game design, web and graphic design, and other areas where modern media is produced. A companion website to this book includes a glossary of terms, chapter PowerPoints, and sample text banks for instructors"--
Includes bibliographical references and index.
Keywords: Multimedia systems; Digital media